Classification of Unhealthy Chicken based on Chromaticity of the Comb - Bakar M.A.A.A.; Ker P.J.; Tang S.G.H.; Lee H.J.; Zainal B.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Agriculture; Animals; Bacteria; Color; Feature extraction; Learning algorithms; Learning systems; Losses; Supervised learning; Chicken; Chromaticity; Disease outbreaks; Economic loss; Human health; Human observations; Laboratory test; Machine-learning; Performance; Supervised machine learning; Viruses